Single-Cell Fluorescence Analysis of Pseudotemporal Ordered Cells Provides Protein Expression Dynamics for Neuronal Differentiation - Song, Zhichao; Laureano, Alejandra S.; Patel, Kishan; Yip, Sylvia; Jadali, Azadeh; Kwan, Kelvin Y. (Frontiers in Cell and Developmental Biology, 2019)
Stem cell replacement therapy is a potential method for repopulating lost spiral ganglion neurons (SGNs) in the inner ear. Efficacy of cell replacement relies on proper differentiation. Defining the dynamic expression of different transcription factors essential for neuronal differentiation allows us to monitor the progress and determine when the protein functions in differentiating stem cell cultures. Using immortalized multipotent otic progenitors (iMOPs) as a cellular system for SGN differentiation, a method for determining dynamic protein expression from heterogeneous cultures was developed. iMOP-derived neurons were identified and ordered by increasing neurite lengths to create a pseudotime course that reflects the differentiation trajectory. The fluorescence intensities of transcription factors SOX2 and NEUROD1 from individual pseudotemporally ordered cells were measured. Individual cells were grouped by K-means clustering and the mean fluorescence intensity for each cluster determined. Curve fit of the mean fluorescence represented the protein expression dynamics in differentiating cells. The method provides information about protein expression dynamics in differentiating stem cell cultures.